IDENTIFICATION OF THE VIRUS DENGUE–3 EPITOPE’S IMMUNODOMINAN USING THE SYNTHETIC PEPTIDE - Nirwati, Hera; ., Sutaryo; Wahyono, Djoko (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
Dengue virus infection has been known as an important health problem in many tropical countries, because of increasing number of patients, expansion of epidemic areas and emergence of severe clinical manifestations. Dengue virus consists of 3 structural and 7 nonstructural proteins. The major virion surface protein, the envelope protein, is the most important antigen with regards to virus biology and humoral immunity. Synthetic peptide derived from the envelope protein gene sequence can be used to identify region of the envelope protein that elicits antibodies. One hundred and sixty-one synthetic peptides were synthesized based on sequence of protein envelope dengue-3 virus published by Osatomi and Sumiyoshi. Each peptide consists of 15 amino acids with the last 12 amino acids overlapped. Peptide synthesizer, auto-spot robot ASP 222 (Abimed), was used for synthesis using solid spot method developed by Ronald Frank. Synthetic peptides attached to nitrocellulose membrane were used for spot immunoassay of 6 normal human sera, 6 dengue infected human sera and 6 non dengue-infected. Nine peptides were specific for dengue infected sera and these might be candidate immunodominat epitopes of dengue virus-3. They were EGLSGATWVDVVLEH (amino acids number 13-27), VCKHTYVDRGWGNGC (91-105),SIEGKVVQHENLKYT (124-138), TVHTGDQHQVGNETQ (142-156), TLGLECSPPTGLDFN (178-192), KGEDAPCKIPFSTED (325-339), PFSTEDGQGKAHNGR (334-348), GARRMAILGDTAWDF (406-420) and KIGIGVLLTWIGLNS (454-468). Based on spot immunoassay, 11 peptides were synthesized and used them for ELISA of 15 normal sera, 22 non-dengue infected sera and 37 dengue sera. Peptides BTLDDIELQKTEATQLA, BPFSTEDGOGKAHNGR and BKKEEPV NIEAEPPFG showed significantly different in their reactivities to the three groups. Combinations of two peptides were used for ELISA. Only one of them (BKGEDAPOKIPFSPED and BRMAILGD TAWDFGSV) showed significantly different in their reactivi- ties to the three groupsKey words: synthetic peptide, envelope protein dengue-3, spot immunoassay